Anxiolytic-Like Effects of Bergamot Essential Oil Are Insensitive to Flumazenil in Rats. (14th August 2019) - Rombolà, Laura; Scuteri, Damiana; Adornetto, Annagrazia; Straface, Marilisa; Sakurada, Tsukasa; Sakurada, Shinobu; Mizoguchi, Hirokazu; Corasaniti, Maria Tiziana; Bagetta, Giacinto; Tonin, Paolo; Morrone, Luigi Antonio
Abstract : Anxiety disorders are one of the most common mental disorders, and benzodiazepines (BDZs), acting on gamma-aminobutyric acid type A (GABA-A) receptor complex, represent the most common antianxiety medications in the world. However, chronic BDZ use elicits several adverse reactions. Reportedly, aromatherapy is safer for the management of anxiety. Bergamot essential oil (BEO) extracted from Citrus bergamia Risso et Poiteau fruit, like other essential oils, is widely used in aromatherapy to relieve symptoms of stress-induced anxiety. Interestingly, preclinical data indicate that BEO induces anxiolytic-like/relaxant effects in animal behavioural tasks not superimposable to those of benzodiazepine diazepam. To better elucidate the involvement of GABAergic transmission, the present study examines the effects of pretreatment with flumazenil (FLZ), a benzodiazepine site antagonist, on BEO effects using open-field task (OFT) in rats. The data yielded show that FLZ does not significantly affect behavioural effects of the phytocomplex. These results demonstrate the lack of overlapping between BEO and BDZ behavioural effects, contributing to the characterization of the neurobiological profile of the essential oil for its rational use in aromatherapy.